Thrombolysis With Single Bolus Tenecteplase Compared With Streptokinase Infusion in the Treatment of Acute Pulmonary Embolism: A Pilot Study. (September 2015) - Patra, Soumya; Nagesh, C. M.; Reddy, Babu; Srinivas, B. C.; Agrawal, Navin; Manjunath, C. N.; Hegde, Madhav
Objective: This study was planned to compare the efficacy of bolus regimens of tenecteplase (TNK) and 24 hours infusion of streptokinase (STK) in acute pulmonary embolism (APE) in a resource-poor setting. Interventions: In all, 25 patients received injection of TNK, and 75 patients received infusion of STK over 24 hours. Results: Pulmonary artery systolic pressure and right ventricular function were improved separately and significantly ( P = .01) in both the study groups of patients from baseline at 24 hours or at seventh day and was comparable among the TNK and STK groups of patients. Mean duration of stay in intensive care unit was significantly less (2.2 ± 0.8 vs 3.2 ± 1.3 days; P = .04), and bleeding risk was also found to be nonsignificantly less in the TNK group. Conclusion: These results suggest that a 24-hour infusion regimen of STK is as effective as bolus TNK in the treatment of patients with APE in countries with limited resources.